Infrared spectroscopy and onychomycosis. (1st March 2019) - De Bruyne, S.; Speeckaert, R.; Boelens, J.; Hayette, M‐P.; Speeckaert, M.; Delanghe, J.
Summary: Onychomycosis is a fungal infection of the nail. During recent decades, the rate of onychomycosis has been rising globally in relation to increases in important risk factors (e.g. diabetes mellitus) and lifestyle changes (e.g. occlusive footwear). Tests commonly used in the diagnosis of onychomycosis (such as potassium hydroxide preparation, histopathological examination with periodic acid‐Schiff stain and culture) are either time‐consuming or require specially trained personnel. Infrared spectroscopy allows doctors to look more closely at the skin than with the naked eye. Recently, the field of infrared spectroscopy has expanded into new and exciting uses due to significant improvements in the instruments used and the development of new techniques. The technique presents attractive features such as being fast, simple, non‐destructive and even portable. Furthermore, a minimum level of expertise is required with relatively low setup costs, i.e. one‐time fixed cost for the spectrometer. The aim of this study was to determine whether 'Attenuated total reflectance Fourier transform infrared' (ATR‐FTIR) spectroscopy can detect and differentiate causes of onychomycosis both in the lab and in patients. The study concluded that organisms that cause onychomycosis can be detected and differentiated in an easy and fast way by means of ATR‐FTIR spectroscopy. However, large‐scale investigations are necessary to determine its definite position compared to currently employed techniques.